Living Mantra Mantra, Deity, and Visionary Experience Today - Rao, Mani (Contemporary Anthropology of Religion,, 2019)
Living Mantra is an anthropology of mantra-experience among Hindu-tantric practitioners. In ancient Indian doctrine and legends, mantras perceived by rishis (seers) invoke deities and have transformative powers. Adopting a methodology that combines scholarship and practice, Mani Rao discovers a continuing tradition of visionaries (rishis/seers) and revelations in south India's Andhra-Telangana. Both deeply researched and replete with fascinating narratives, the book reformulates the poetics of mantra-practice as it probes practical questions. Can one know if a vision is real or imagined? Is vision visual? Are deity-visions mediated by culture? If mantras are effective, what is the role of devotion? Are mantras language? Living Mantra interrogates not only theoretical questions, but also those a practitioner would ask: how does one choose a deity, for example, or what might bind one to a guru? Rao breaks fresh ground in redirecting attention to the moments that precede systematization and canon-formation, showing how authoritative sources are formed.